PENGARUH RETURN ON ASSET (ROA), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM PADA PT UNILEVER INDONESIA TBK PERIODE 2013-2024 - Prasetyo, Agung Slamet; Ningrum, Diah Ayu Puspita (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study aims to determine the effect of financial ratios on stock returns at PT Unilever Indonesia Tbk during the period 2013-2024. The financial ratios studied were Return on Assets (ROA), Net Profit Margin (NPM), and Earnings Per Share (EPS). The data collection technique used was documentation. The sampling technique used was purposive sampling. The data analysis method used was multiple linear regression. The results showed that ROA, NPM, and EPS did not significantly influence stock returns, either partially or simultaneously.